18.7k views
0 votes
Solve the equation after making the appropriate substitution. Need help!

Solve the equation after making the appropriate substitution. Need help!-example-1

1 Answer

3 votes

Answer:

Explanation:

First realize that


(x^(1/3))^(2)=x^(2/3)

Usually when you are asked to solve making a substitution you need to find substitute a term leaving a quadratic equation.

if you replace:


x^(1/3)=u


u^(2)-3u-18 = 0 \\(u-6)(u+3)= 0 \\u = 6 \\u = -3 \\x^(1/3) = 6 => x = 6^(3) = 216\\x^(1/3) = -3 => x = (-3)^(3) = -27

User Apurva
by
5.3k points